Analisis Pembentukan Portofolio Saham Optimal Menggunakan Model Indeks Tunggal (Studi Empiris Pada Perusahaan BUMN yang Terdaftar Dalam LQ45 di Bursa Efek Indonesia) - Rahmat Suharnas; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to use the Single Index Model to form an optimal stock portfolio on the LQ45 index from August 2020 to January 2023. This study aims to determine the proportion of funds allocated to each stock and calculate the return and risk associated with the optimal stock portfolio. formed. The research design used is quantitative descriptive. The research population consists of BUMN shares listed on the LQ45 index on the Indonesia Stock Exchange between August 2020 and January 2023. The research sample was selected through purposive sampling, namely by targeting BUMN shares which remained consistently listed on the LQ45 index during the above period. With this approach, a research sample consisting of 9 stocks was selected. The results showed that of the 9 stocks, 6 stocks met the criteria for inclusion in the optimal portfolio based on the Single Index Model. The proportion of funds to be invested in each stock in the optimal portfolio is as follows: BMRI (Bank Mandiri (Persero) Tbk.) 24.89%, ANTM (Aneka Tambang Tbk.) 11.40%, PTBA (Bukit Asam Tbk.) of 12.01%, BBNI (Bank Negara Indonesia (Persero) Tbk.) of 24.45%, BBRI (Bank Rakyat Indonesia (Persero) Tbk.) of 18.33%, and PGAS (Perusahaan Gas Negara Tbk.) of 8.91%. The optimal stock portfolio formed from the above allocation of funds produces a return of 2.36% per month, with a risk of 1.15% that must be borne by investors.Keywords: Optimal Stock Portfolio, Single Index Model, LQ45 Index, Return and Risk.